AL-TASĀMUH OR TOLERANCE IN THE QURAN AND SUNNAH AND CLAIMS OF THE DENIERS - Klaina, Mekki; Putra, Ansusa (Living Islam: Journal of Islamic Discourses, 2024)
This research examines the topic of al- Tasāmuh in the Quran and Sunnah and how it aligns with the meaning declared in 1995. It is evident that there is a difference in meaning between the two. Those who deny al- Tasāmuh in Islam rely on a different concept that seeks to separate from religious and cultural identity and rely on secularism. This research shows that the scope of tolerance is wide in Islam, which gives Muslims and non-Muslims the right to coexist in safety. It is connected with what a person has the right to be tolerant in. As for Allah's rights, they do not fall under this right. Moreover, freedom has limits to prevent self-harm or harming others. Islam does not impose religion on people, but focuses on dialogue and persuasion. To promote positive tolerance, emphasis should be placed on teaching future generations how to interact with others, and laws should protect the rights of all without tolerance for disrespect for religious sanctities or the spread of deviant behavior. Keyword: Al-Tasāmuh; Tolerance; Quran and Sunnah; Islamophobia.   Kajian ini membahas tentang topik al-Tasāmuh dalam Al-Quran dan Sunnah serta sejauh mana maknanya sesuai dengan apa yang disebutkan oleh UNESCO pada tahun 1995. Jelas sekali ada perbedaan makna di antara keduanya. Mereka yang menolak al-Tasāmuh dalam Islam mengandalkan berbagai konsep yang mencoba memisahkan diri dari identitas agama dan budaya serta mengandalkan sekularisme. Kajian ini menunjukkan bahwa ruang lingkup toleransi dalam Islam sangat luas, yang memberikan hak kepada umat Islam dan non-Muslim untuk hidup bersama dengan aman. Itu terkait dengan apa yang menjadi hak seseorang untuk toleran. Kebenaran Tuhan tidak termasuk dalam kebenaran ini. Selain itu, kebebasan memiliki batasan untuk mencegah kerugian bagi diri sendiri atau orang lain. Islam tidak memaksakan agama pada manusia, tetapi berfokus pada dialog dan persuasi. Untuk mempromosikan toleransi positif, perlu ditekankan pendidikan generasi mendatang tentang bagaimana berinteraksi dengan orang lain, dan undang-undang harus melindungi hak-hak semua orang tanpa menoleransi kerusakan kesucian agama atau berupaya menyebarkan perilaku menyimpang. Kata kunci: Al-Tasāmuh; Toleransi; Quran dan Sunnah; Islamofobia